How does climate policy uncertainty influence energy consumption transition in China: evidence from 277 cities - Wei, Yake; Xiao, Zeliang; Sun, Liyang (Frontiers in Environmental Science, 2026)
Energy consumption transition is fundamental to achieving carbon neutrality without sacrificing development in developing economies. China’s experience under its dual-carbon targets and evolving climate governance provides a valuable case. Using panel data from 277 Chinese prefecture-level cities from 2007 to 2023, this study applies two-way fixed effects models and spatial Durbin models to assess the impact of climate policy uncertainty on urban energy consumption transition. The results show that higher climate policy uncertainty significantly impedes energy consumption transition, particularly in resource-based, highly marketized, and rapidly developing eastern cities. This inhibitory effect operates through both supply and demand channels, weakening industrial chain resilience, suppressing corporate green innovation disclosure, and dampening public environmental awareness. Spatial analysis further reveals substantial negative spillovers, with the effect of climate policy uncertainty on neighboring energy consumption transition roughly six times stronger than its local impact. The findings highlight that proactively managing climate policy uncertainty is essential for enabling a stable and effective energy consumption transition, offering a practically relevant reference for developing countries to anticipate and manage governance challenges on the path to sustainable growth.